PENERAPAN MODEL BERMAIN PERAN PADA PEMBELAJARAN BIOLOGI MATERI KODE GENETIK DAN SINTESIS PROTEIN DI SMA NEGERI 1 INDRALAYA UTARA - Frisca Novianty Sinaga; Siti Huzaifah; Lucia Maria Santoso (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2016)
Abstract: This study aimed to find out the effect of role playing model of teaching on students’ achievement of  protein synthesis. This study was conducted at SMA Negeri 1 Indralaya Utara (South Sumatera, Indonesia), academic year 2015/2016. This study using pre-experimental method with one-group pretest-posttest design at 30 students’ of  XII IPA-2. The sample of this study was taken using simple random sampling. Data collected by the method of testing for cognitive learning achievement (knowledge), by the method observation for students’ activities, and by the method of the questionnaire for students’ responses of the implementation for the model of teaching. Activities and responses data are the supporting data in the study. The collected data was analyzed using t-test and descrptive statistic. Result showed there is a significant effect of role playing model on students’ achievement. The mean score of the students’ achievement (n-gain) was 1,84 with high categorize. The mean score of the students’ activities (motoric, visual, oral, writting activities) was 85,12, categorized into very active. The mean score of the students’ response was 78,11, categorized into good.   Kata Kunci: Activities, learning achievement, role playing model, responses, protein synthesis